2023
DOI: 10.1111/head.14625
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy may protect the brain against prolonged consequences of headache attacks: A narrative/hypothesis review

Michal Fila,
Elzbieta Pawlowska,
Joanna Szczepanska
et al.

Abstract: ObjectiveTo assess the potential of autophagy in migraine pathogenesis.BackgroundThe interplay between neurons and microglial cells is important in migraine pathogenesis. Migraine‐related effects, such as cortical spreading depolarization and release of calcitonin gene–related peptide, may initiate adenosine triphosphate (ATP)‐mediating pro‐nociceptive signaling in the meninges causing headaches. Such signaling may be induced by the interaction of ATP with purinergic receptor P2X 7 (P2X7R) on microglial cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 128 publications
0
3
0
Order By: Relevance
“…Several reports suggest a link between autophagy and ferroptosis underlined by the involvement of autophagy in the regulation of iron-dependent lipid peroxidation and RONS production during ferroptosis ( Lee et al, 2023 ). We have recently argued that an interplay between degradative autophagy in neurons and secretory autophagy in the glia might protect the brain against prolonged consequences of migraine attacks ( Fila et al, 2023b ). Therefore, ferroptosis may be coupled with autophagy in migraine.…”
Section: Ferroptosis Ferritinophagy and Their Potential In Migrainementioning
confidence: 99%
See 1 more Smart Citation
“…Several reports suggest a link between autophagy and ferroptosis underlined by the involvement of autophagy in the regulation of iron-dependent lipid peroxidation and RONS production during ferroptosis ( Lee et al, 2023 ). We have recently argued that an interplay between degradative autophagy in neurons and secretory autophagy in the glia might protect the brain against prolonged consequences of migraine attacks ( Fila et al, 2023b ). Therefore, ferroptosis may be coupled with autophagy in migraine.…”
Section: Ferroptosis Ferritinophagy and Their Potential In Migrainementioning
confidence: 99%
“…Autophagy raises an emerging interest in the study of the pathogenesis of various diseases, but there is a lack of experimental or clinical studies showing the involvement of autophagy in migraine pathogenesis. However, increased iron deposits in certain areas of the brain may be a source of many substrates for both degradative and secretory autophagy ( Fila et al, 2023b ). Iron deposited in the brain may stimulate ferritinophagy, which interplays with ferroptosis and may disturb nociceptive signaling important in migraine.…”
Section: Conclusion Perspectives and Outstanding Questionsmentioning
confidence: 99%
“…On the other hand, several studies with long-lived organisms showed that delayed aging was associated with increased autophagy [91][92][93][94]. Recently, we suggested that an interplay between secretory autophagy in microglia and degradative autophagy in neurons may play a role in migraine pathogenesis with the involvement of brain-derived neurotrophic factor (BDNF) and the interaction of ATP with the purinergic receptor P2X7 (P2X7R) [95]. It was observed that a ketogenic diet upregulated hepatic autophagy in mice [96].…”
Section: The Ketogenic Diet and Ketone Bodies In Agingmentioning
confidence: 99%